Spinal Alterations of Reil Insula in Alzheimer's Disease. (June 2017) - Petrides, Foivos E.; Mavroudis, Ioannis A.; Spilioti, Martha; Chatzinikolaou, Fotios G.; Costa, Vasiliki G.; Baloyannis, Stavros J.
Alzheimer's disease (AD) is a progressive neurodegenerative disease that involves numerous cellular and biochemical mechanisms resulting in synaptic alterations and extensive neuronal loss. It is primarily characterized by impairment of memory, associated frequently with mood disorders. Continuous studies have shown that insula may be an important target of AD, but neuropathological alterations have not been described extensively. In the present study, we attempted to describe the morphometric and morphological changes of the spines of Reil insula in AD in comparison with normal aging using a silver impregnation technique. We classified spines into 3 types: (1) long neck, (2) short stubby, and (3) other types; and we measured and correlated the length of them in normal controls and in individuals with AD using ImageJ application. Statistical analysis was based on the Student t test on the basis of 360 cells in SPSS v.17.0, and significance was taken as P < .05.